Temperature calculation of the tool and chip in slicing process with equal-rake angle arc-tooth slice tool. (September 2020) - Wu, Xiaoqiang; Li, Jia; Jin, Yongquan; Zheng, Shuxian
Highlights: An analytical temperature model for tool and chip of slicing process is established. The micro-angle tooth is proposed for the equal-rake angle arc-tooth slice tool. The temperature of the chip and rake face is calculated and verified. Abstract: As a new gear processing technology, gear slicing technology has the characteristics of high efficiency, high precision and environmental protection. In this paper, the slicing process with equal-rake angle arc-tooth slice tool (ERA-ATST) is taken as the research object. Considering the particularity of the slicing process, a theoretical calculation method of tool and chip temperature is proposed. By analyzing the characteristics of the slicing process with ERA-ATST, a cutter tooth of the ERA-ATST is divided into several sections along the cutting edge, which are called micro-section tooth. For each of the micro-section tooth, the slicing process is simplified and equivalent to oblique cutting process. Comprehensively considering the influence of cutting speed, chip force and tool-chip contacting characteristics in slicing process, a temperature calculation model is established based on the generation mechanism of slicing heat. The tool and chip temperature is derived by averaging the results of several micro-section teeth. With the established model, an inner arc-spur gear slicing with the ERA-ATST is used as an example to calculate the temperature on the chip and rake face. The gear slicing test is carried out on the slicing machine tool. The measured chip temperature and rake face temperature are compared with the corresponding calculation results to verify the temperature calculation model. The proposed temperature calculation method provides a theoretical basis for the analysis and control of slicing heat in the gear slicing process.